Chocolate decoration techniques with Ewald Notter. - 4 0 16; Culinary Institute of America; 5 Culinary Institute of America (New York, 2007)
In part one of this DVD, Chef Notter teaches you the fundamentals of chocolate work, bringing all the information and techniques together as he: explains how chocolate is manufactured and tempered ; demonstrates the basics of spraying, cutting out shapes, and using plastic molds and transfer sheets ; creates bunnies and chicks, a swan, and Valentine and Christmas displays. Stretch your creativity and build on the techniques you explored in part one. In part two, Chef Notter teaches you how to: make chocolate shavings, curls, and cigarettes ; pipe chocolate to make decorative filigrees and ornaments ; create several fanciful chocolate pieces {u2013} an owl, a rooster, and a hat.
DVD format.
Keywords: 2 -- 0; 6; Chocolate.;Chocolate molds.;Chocolate processing.;Chocolate desserts. -- 20; 20; 2